The Malacca Strait separates distinct faunas of poorly-flying Cautires net-winged beetles - Jiruskova, Alice; Motyka, Michal; Bocek, Matej; Bocak, Ladislav (PeerJ, 2019)
We investigated the spatial and temporal patterns of Cautires diversification on the Malay Peninsula and Sumatra to understand if the narrow and frequently dry Malacca Strait separates different faunas. Moreover, we analyzed the origin of Cautires in Malayan and Sumatran mountains. We sampled 18 localities and present the mtDNA-based phylogeny of 76 species represented by 388 individuals. The phylogenetic tree was dated using mtDNA evolution rates and the ancestral ranges were estimated using the maximum likelihood approach. The phylogeny identified multiple lineages on the Malay Peninsula since the Upper Eocene (35 million years ago, mya) and a delayed evolution of diversity in Sumatra since the Upper Oligocene (26 mya). A limited number of colonization events across the Malacca Strait was identified up to the Pliocene and more intensive faunal exchange since the Pleistocene. The early colonization events were commonly followed by in situ diversification. As a result, the Malacca Strait now separates two faunas with a high species-level turnover. The montane fauna diversified in a limited space and seldom took part in colonization events across the Strait. Besides isolation by open sea or a savannah corridor, mimetic patterns could decrease the colonization capacity of Cautires. The Malay fauna is phylogenetically more diverse and has a higher value if conservation priorities should be defined.
Keywords: Oriental region; Colonization; Molecular phylogeny; Mimicry